Imputability of Azathioprine in the Occurrence of Chronic Myeloid Leukemia in Crohn's Disease: An Exceptional Case Report - Zaimi, Yosra; Bouksir, Chayma; Ayadi, Shema; Ayari, Myriam; Ksontini, Feryal L. (Current Drug Safety, 2023)
Background: Patients with Cohn’s disease (CD) treated with thiopurines are at an increased risk of developing cancer. Leukemias are less frequent than other hematopoietic tumors and the development of Chronic myeloid leukemia (CML) after immunosuppression has not been proven. Case Report: We describe the case of a 61-year-old female who developed a CML after 8 years of treatment with azathioprine (AZA) for ileal Crohn’s disease associated with a duodenal localization. We reviewed the current evidence on the interactions between CD, CML and AZA as well as the potential underlying mechanisms of leukemia in AZA-treated patients. Conclusion: We concluded that the pathogenesis of CML is multifactorial in CD. The nature of the association between AZA and CML in CD patients warrants further investigation.
Keywords: thiopurines